Games untold ebook - Barnes, Jennifer Lynn (The Inheritance Games, 2024)
OVER 5 MILLION COPIES SOLD OF THE #1 BESTSELLING SERIES! Romance, luxury, and secrets abound in this thrilling new collection that takes readers deeper into the world of the #1 bestselling Inheritance Games series   There is nothing frivolous about the way a Hawthorne man loves.   An amnesiac playboy and the woman with every reason to hate him. A daredevil, his favorite heiress, and three nights in Prague. An unlikely pairing between a cowboy and a goth. Four brothers with an inescapable bond, strengthened by the family they chose, in a house of wonders that promises to always deliver one more secret.    Discover their stories of love and loss, power, puzzles, and life-and-death secrets in this mind-blowingly romantic collection that proves that when you love the way Hawthornes love, there is no going back.   This collection includes: That Night in Prague (novella) The Same Backward as Forward (novella) The Cowboy and the Goth Five Times Xander Tackled Someone (and One Time He Didn’t) $3CR3T $@NT@ One Hawthorne Night* What Happens in the Treehouse*  Pain at the Right Gun *previously published in limited release Don’t miss a moment of The Inheritance Games Saga, including the Grandest Game, the thrilling new series set in the world of the Inheritance Games .    Reading them all? The ideal reading order is : The Inheritance Games, The Hawthorne Legacy, The Final Gambit, The Brothers Hawthorne, The Grandest Game, Games Untold,  and Glorious Rivals.    Looking for more unputdownable reads from Jennifer Lynn Barnes? Check out The Naturals series  (The Naturals, Killer Instinct, All In, Bad Blood,  and the enovella,  Twelve) , The Debutantes duet ( Little White Lies, Deadly Little Scandals),  and  The Lovely and the Lost .